2020
DOI: 10.21203/rs.3.rs-56923/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of human sodium leak channel NALCN in complex with FAM155A

Abstract: NALCN, a sodium leak channel mainly expressed in the central nervous systems, is responsible for the resting Na+ permeability that controls neuronal excitability. Dysfunctions of the NALCN channelosome, NALCN with several auxiliary subunits, are associated with a variety of human diseases. Here, we reported the cryo-EM structure of human NALCN in complex with FAM155A, at an overall resolution of 3.1 angstrom. FAM155A forms extensive interactions with the extracellular loops of NALCN that help stabilize NALCN i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Architecture of the NALCN-FAM155A-UNC79-UNC80 quaternary complex. Previous structural studies on the NALCN-FAM155A heterodimer showed that this subcomplex is wellfolded in the absence of UNC79 and UNC80 [15][16][17] . However, both UNC79 and UNC80 are crucial for the NALCN currents in HEK293T cells 1 , indicating that UNC79 and UNC80 might not be necessary for channel folding, but rather affect the plasma membrane localization of the channel or play other regulatory roles.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Architecture of the NALCN-FAM155A-UNC79-UNC80 quaternary complex. Previous structural studies on the NALCN-FAM155A heterodimer showed that this subcomplex is wellfolded in the absence of UNC79 and UNC80 [15][16][17] . However, both UNC79 and UNC80 are crucial for the NALCN currents in HEK293T cells 1 , indicating that UNC79 and UNC80 might not be necessary for channel folding, but rather affect the plasma membrane localization of the channel or play other regulatory roles.…”
Section: Resultsmentioning
confidence: 94%
“…1b), suggesting they could form a stable heterodimer. However, the quaternary complex tends to dissociate during purification 16,17 , probably due to the low affinity between the NALCN-FAM155A subcomplex and UNC79-UNC80 heterodimer. To overcome this obstacle, we exploited the tight binding between GFP and its nanobody 19 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported the structure of human NALCN-FAM155A subcomplex, revealing that FAM155A stabilizes NALCN by attaching to the extracellular loops of NALCN 17 . UNC79 and UNC80, however, were invisible in the previous structure, although they were co-expressed with NALCN and FAM155A.…”
Section: Introductionmentioning
confidence: 99%
“…However, the auxiliary subunits of the NALCN channelosome are unique and share no sequence homology to the auxiliary subunits of other 4 × 6 TM channels. Among the auxiliary subunits, FAM155A may facilitate the folding and membrane translocation of NALCN through forming a stable subcomplex with NALCN [17][18][19] . UNC79 and UNC80 are large proteins that have been reported indispensable for neuronal localization in mice 9 and robust circadian locomotor rhythms in Drosophila 6 .…”
Section: Introductionmentioning
confidence: 99%